Impact of Service Quality, Product Excellence, and Timely Delivery on Customer Satisfaction in Lazada’s E-Commerce Platform - Muhamad Amirulloh; Muhammad Akbar Kadapi; Ramlah Puji Astuti (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the impact of service quality, product quality, and delivery punctuality on customer satisfaction in Lazada’s e-commerce platform. Using a quantitative approach with purposive sampling, data were collected from 333 Lazada users. Validity, reliability, and multiple linear regression analyses were applied. Results show that service quality and product quality significantly influence customer satisfaction (p = 0.001), while delivery punctuality does not (p = 0.778). Simultaneous testing indicates a significant combined effect of all variables (p = 0.000). The R² value of 0.139 suggests that 13.9% of satisfaction variance is explained by the studied variables. The study highlights the importance of service and product quality, and recommends further exploration of other influencing factors such as pricing and user experience.